2013
DOI: 10.1158/1541-7786.mcr-12-0685-t
|View full text |Cite
|
Sign up to set email alerts
|

RASEF is a Novel Diagnostic Biomarker and a Therapeutic Target for Lung Cancer

Abstract: Genome-wide gene expression profiling revealed that the Ras and EF-hand domain containing (RASEF) transcript was significantly transactivated in the majority of lung cancers. Using lung cancer cells, transient expression of RASEF promoted cell growth, whereas RASEF knockdown not only reduced its expression but resulted in growth suppression of the cancer cells. Immunohistochemical staining using tumor tissue microarrays consisting of 341 archived non-small cell lung cancers (NSCLC) revealed the association of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The expression of RASEF, which encodes a member of the Rab family of GTPases, was found to be higher in breast tumors than in cutaneous malignant melanoma lesions [15]. In addition, Oshita et al suggested that RASEF overexpression might promote lung cancer cell proliferation by enhancing extracellular signal-regulated kinase (ERK) 1/2 signaling and that RASEF might be a poor prognostic marker in lung cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of RASEF, which encodes a member of the Rab family of GTPases, was found to be higher in breast tumors than in cutaneous malignant melanoma lesions [15]. In addition, Oshita et al suggested that RASEF overexpression might promote lung cancer cell proliferation by enhancing extracellular signal-regulated kinase (ERK) 1/2 signaling and that RASEF might be a poor prognostic marker in lung cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, a more definitive characterization of RASEF as a tumor suppressor will require in vivo models. Notably, RASEF has been previously reported to have differential functions depending on the cancer type; it has been attributed with a tumor‐suppressive function in myeloid leukemia (Nakamura et al., ), while it has an oncogenic function in lung cancer (Oshita et al., ). Our study is consistent with a model in which RASEF acts as a tumor suppressor in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Rab45 represents a novel diagnostic biomarker and a potential therapeutic target for lung cancer [70,71]. KD of Rab45 by siRNA results in a significant decrease in the cell growth of NSCLC [70]. Conversely, Rab45 has also been implicated as a tumor suppressor.…”
Section: Rabs That Regulate Mitochondrial Membrane Potentialmentioning
confidence: 99%